The Impact of a Flipped Classroom on the Creativity of Students in a Cake Decorating Art Club - Tien, Li-Chu; Lin, Shih-Yen; Yin, Hsiang; Chang, Jen-Chia (Frontiers in Psychology, 2020)
This study explored the effect of learning strategies in a student organization on cake art creativity. The participants were 27 student members of a cake decorating art club from one central university in Taiwan. A quasi-experimental pretest-posttest design was adopted, with 90 h of experimental teaching over 16 weeks. The results, which included the use of a questionnaire, classroom observation, and in-depth interviews, suggest that in terms of creativity, the group participating in flipped classroom learning significantly outperformed the group using traditional learning strategies. Furthermore, flipped classroom learning promoted learner motivation and satisfaction.